Neurolinguistic programming as an innovative strategy for language and literature teaching - Riera–Flores , Michelle (2021)
This article is the result of research with a quali-quantitative approach. The purpose was to collect information and theoretical data to understand and explain how Neurolinguistic Programming (NLP) can through the new studies of Language and Literature Didactics (DLL) contribute to its development.  The aim is to get teachers to connect with the world of students. NLP strategies have been adapted to language classes in a didactic way and the role of emotions in the development of the teaching-learning process is taken into account. The statistical data obtained through a descriptive survey helped to understand how teachers work with students and how they respond to the applied learning model. Therefore, it was concluded that this model does not respond to current needs. The proposal proposed provides new tools to the teacher to achieve significant learning taking into account the needs and interests of students. For this, the study is centered in the different techniques of the NLP, applicable in the classroom as: knowledge of the representational systems that exist to feel and know the world that surrounds us, how the levels of logical thought work and how they affect the behavior, rapport strategies to tune in group and even strategies to improve the spelling with the NLP.